A historical view of the U.S.middle east policy: the period of Obama administration (Journal of history, 2021)
This research work examines the historical aspects of the Middle East policy of the United States, conducted by Obama administration. The aim of this investigation is to clarify “soft (smart) power” policy of B. Obama government and to illustrate the impacts and regional events, occurred at the result of this policy.There were made some summarizes on such points as public diplomacy of the United States, facts about the Arab Spring and the consequences of this political event to the attitude of the USA to Middle Eastern countries (Iran, Turkey, Israel and so on).This research was made on the ground of various sources (periodicals, books, articles and internet sources) that clarified major aspects of the investigated topic, as well as there was obtained general hy- pothesis and consequences of the investigation. Consequently, Obama administration did not realize the theory of soft power in the Middle East region entirely. The attitude to Iran, which based on this theory concluded with disagreement between U.S. and her stable military, economic and political allies in the Middle East region. The challenge for democratization in the Persian Gulf and Middle East regions on the ground of “Arab Spring” did not establish stability and pro-Western authority in these regions; otherwise, this political confrontation caused to the acceleration of anarchy and growth of the number of states that became to be governed by Islamic rules and which criticized pro- American countries. The relations of the United States with her regional partners and key actors of the Middle East – Turkey and Israel aggra- vated at the result of “soft power” of Obama administration. Historical outlook shows that, the policy of Obama administration deeply altered the regional circumstances and leadership position of the United States in the Middle East, as well as strained political confrontation in this region.Key words: the Middle East, USA, Obama administration, “soft power”, Arab Spring.